The Virtual and Bimodal Courses as a Tool for the Updating of Teachers of Social Studies and Civic Education - Barquero Ruiz, Alejandra (2018)
The present work exposes the results obtained within the Bimodal Continuing Education project promoted by the School of History of the National University of Costa Rica during the year 2017. This project has a validity of three years, beginning work in 2016. The project aims to implement virtual and bimodal courses as an update strategy for the Social Studies and Civic Education faculty. The academic activity has been valued in a positive way by providing teachers from all over the country with updating options using technological resources, allowing them to combine their daily tasks with updating activities that can be applied in the place and time they wish. Therefore, courses that combine virtuality with hybrid learning –blended learning– are becoming increasingly necessary in university contexts as a way to extend academic work and support the graduate community.